Pengeringan Cabe Merah dengan Menggunakan Energi Panas Pembuangan Air Conditioner (AC) - Tamrin, Tamrin; Waluyo, Sri; Novita, Dwi Dian (Jurnal Agricultural Biosystem Engineering, 2024)
Drying of red chili will be done if the chili is needed for storage or for making chili powder. Drying of chili is done by flowing hot air. Chili is placed on a rack and hot air is flowed through the pile of chili, so that the chili will dry according to the duration of heating. Heat energy is used as waste heat from the AC. The use of this heat is to utilize energy that is currently still being released into the air. Its utilization is by making shelves and placing chili on the rack. . Hot air is flowed through the shelves. The study was conducted by drying 9 kg of chili on 3 racks. Observations made were the temperature of the drying air, water content, changes in chili color and changes in the weight of chili and vitamin C. The results of the study showed that the heat of the exhaust air from the AC can reach 42 oC with RH 48 - 63%. Drying chili from 83% water content to 9% water content requires a drying time of 50 hours or 7 days. The vitamin C content of chilies dried using AC heaters is lower than drying them in the sun. The red color of dried chilies is higher when dried using AC exhaust heat than when dried in the sun. Keyword: Chili, Color, drying, heat of AC exhaust, water content.